Modern problems and prospects for the development of the estimate business in the construction of the republic of Kazakhstan - Zhigulina, A.Yu.; Shinguzhieva, A. B.; Nazhmedenova, S. Y.; Maksotova, A. B.; Abzalqyzy, A. (ЗКАТУ им. Жангир хана, 2024)
Estimating is one of the main parts of construction production, which is a combination of methods and means that are used to determine the cost of all construction and installation work, as well as the costs of operation and repair of buildings and structures. The paper shows a literature review of foreign research articles on cost estimates in construction. The problems of pricing, as well as modern problems and prospects for the development of cost estimates in construction are considered and investigated. The basic requirements and conditions for pricing in construction in Kazakhstan are presented, including some features of the formation of the construction price of an object. An analysis was made of the main directions of reforming estimate regulation and pricing, as well as the prospects for introducing new technologies into estimate activities. Options for the use of computer technologies (computer products) in calculating the estimated cost of construction are considered, options for the development of estimating in construction are proposed, which includes automation of the costing process (estimate programs ABC-4, SANA), development of information and BIM technologies, improvement of the personnel training system and regulatory framework, creating an improved effective price control system.
Modern problems and prospects for the development of the estimate business in the construction of the republic of kazakhstan / A.Yu. Zhigulina, A. B. Shinguzhieva, S. Y. Nazhmedenova, A. B. Maksotova, A. А. Abzalqyzy. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 1-2 (74). Ч. ІІ. - Р. 250-258. - ISSN 2305-9397
Keywords: regulatory framework; calculation; automation; pricing; problems